Increasing Learning Outcomes Through Strengthening the Snowball Throwing Learning Model - Tetep; Agisna Putri Nurahmi (Journal Civics And Social Studies, 2021)
Learning outcomes are basically influenced by many factors, one of which is the use of learning methods. Teacher creativity in presenting learning material using various methods has implications for the low quality of social studies learning outcomes which has an impact on students' low interest in learning. Through experimental research on social studies learning using the Snowball Throwing Method, researchers examined the results of social studies learning using this method, can the snowball throwing method improve social studies learning outcomes for the better? An experimental study conducted on class VIII students at SMP 1 Samarang showed that student learning outcomes before implementing the snowball throwing learning model in social studies subjects were still low because the teacher prepared an interesting learning model, not knowing what the teacher had to do. when students feel less enthusiastic about learning, especially in social studies subjects, when student learning outcomes after applying the social studies learning model become better or can be said to have improved compared to previous learning outcomes. The snowball throwing learning method can improve social studies learning outcomes.